Feral Swine Trapping: Techniques and Designs - Bethany Rose Wight; Raoul Keith Boughton (EDIS, 2018)
Feral swine are an invasive or nuisance species in Florida and most other states because their incessant rooting is ruinous to natural and agricultural habitat. They loosen the soil, destroy native vegetation, and modify the natural chemistry and nutrients of the soil, causing widespread destruction in natural ecosystems, agricultural areas, livestock pastures, and residential areas. They also carry numerous diseases, some of which are transmittable to wild and domestic animals and humans. Trapping and removing swine from your property is an effective way to reduce or control feral swine populations. This 9-page fact sheet written by Bethany Wight and Raoul K. Boughton and published by the UF/IFAS Wildlife Ecology and Conservation Department describes the most commonly used trapping techniques and illustrates several trap and gate designs. https://edis.ifas.ufl.edu/uw440